Biodegradation of diethylketone by Penicillium sp. and Alternaria sp.: a comparative study biodegradation of diethylketone by fungi - Costa, Filomena Natália Araújo (2015)
Two contaminating fungi were isolated from a bioreactor containing diethylketone and Streptococcus equisimilis, subsequently characterized at molecular level and identified as belonging to the Alternaria and Penicillium genera. The ability of these fungi to biodegrade DEK is evaluated. The kinetic parameters are estimated using four growth kinetic models for biodegradation of organic compounds available in literature. The experimental data for Alternaria sp. and Penicillium sp. was found to be better fitted by the Haldane and the Luong respectively. Biodegradation rate kinetics was evaluated using zero-order, pseudo-first order, pseudo-second order and three-half order models. The pseudo-second-order model was found suitable for all the concentrations of DEK tested for the biodegradation assays using Penicillium sp. whereas for the Alternaria sp. this model just describes properly the assays with initial concentrations of DEK higher than 0.5 g/L. The percentage of biodegraded DEK were approximately 100%, for all the initial concentrations tested.